Piccolo and bassoon maintain synaptic vesicle clustering without directly participating in vesicle exocytosis - Mukherjee, Konark (National Academy of Sciences, 2010)
Piccolo and bassoon are highly homologous multidomain proteins of the presynaptic cytomatrix whose function is unclear. Here, we generated piccolo knockin/knockout mice that either contain wild-type levels of mutant piccolo unable to bind Ca(2+) (knockin), ∼60% decreased levels of piccolo that is C-terminally truncated (partial knockout), or <5% levels of piccolo (knockout). All piccolo mutant mice were viable and fertile, but piccolo knockout mice exhibited increased postnatal mortality. Unexpectedly, electrophysiology and electron microscopy of piccolo-deficient synapses failed to uncover a major phenotype either in acute hippocampal slices or in cultured cortical neurons. To unmask potentially redundant functions of piccolo and bassoon, we thus acutely knocked down expression of bassoon in wild-type and piccolo knockout neurons. Despite a nearly complete loss of piccolo and bassoon, however, we still did not detect an electrophysiological phenotype in cultured piccolo- and bassoon-deficient neurons in either GABAergic or glutamatergic synaptic transmission. In contrast, electron microscopy revealed a significant reduction in synaptic vesicle clustering in double bassoon/piccolo-deficient synapses. Thus, we propose that piccolo and bassoon play a redundant role in synaptic vesicle clustering in nerve terminals without directly participating in neurotransmitter release.